Complete Remission of Cutaneous Metastasis from Invasive Breast Cancer with Abemaciclib plus Letrozole - Shaunak N. Valame; Dhruti D. Manek (Indian Journal of Medical and Paediatric Oncology)
Skin metastases from internal malignancies can be the first clinical finding of cancer recurrence. If presentation is delayed, they may ulcerate and develop secondary infection. Through this case, we will highlight a case of breast cancer recurrence with extensive cutaneous metastases that clinically completely responded to oral systemic therapy, thereby obviating the need for chemotherapy and leading to stark improvement in performance status and quality of life.